Sustaining local heritage : fibre art as a new paradigm to uplift Malaysian craft production / Siti Zuraida Maaruf, Ezzah Md Zain and Nabilah Abdullah - Maaruf, Siti Zuraida; Md Zain, Ezzah; Abdullah, Nabilah (Universiti Teknologi MARA, Perak, 2020)
By putting forward contemporary fibre art as a new paradigm in Malaysian craft production, this study aims to uncover how it is applied involving selection of material, utilization of technique right up to the appraisal of resultant product. The underlying rationale is to ensure incessant appreciation of Malaysian crafts by the society, especially the younger generation. This research utilized the Design Development Research (DDR) that consisted of three (3) phases. Selection of research participants used purposive sampling based on the respondents' expertise in the area. In Phase 1, Needs Analysis, was carried out using semi-structured interviews with three (3) textile experts. In Phase 2: Design and Development, the researcher used ADDIE model to develop crafts using fibre art material for Malaysia craft production. In the third and final phase, Implementation and Evaluation, sixty young people from Shah Alam community took part in an assessment of their acceptance of craft using fibre art. However, discussion on this study focuses on the first phase which is the needs analysis. The findings suggest that contemporary fibre art as a new paradigm to Malaysian craft production is relevant and has the potential to be implemented in Malaysia.